Content Analysis On English Moduleâ€œBahasa Inggrisâ€ - Aryani, Dwi ((JELE) Journal Of English Language and Education, 2016)
AbstractThis research is aimed to evaluate the quality of the English module used by students of SMA N 6 Yogyakarta. There were many problems such as mistype, inappropriate content or material, and so on which were found inside the book. Then, the module used by the students should be evaluated on the content to know whether the book met the criteria of good module or not. The research was about case study using content analysis as the method. It used textbook evaluation criteria from Cunningsworth which contained ten aspects of evaluation and compared with the criteria of evaluation from Hutchinson and Waters. The evaluation concerned on the content such as language content and skill, the organization and appearance of the book. The result from Cunningsworth checklist showed that the book got 74. 25% which considered as good book. While the result from Hutchinson and Waters showed 78. 57%. The aspect which got low percentage was vocabulary and reading material, while the rest were considered as good. From evaluation using two concepts from Cunningsworth which compared with the evaluation criteria by Hutchinson and Waters showed a little bit difference. The result showed differences in range 4. 32%.Keywords: module, content analysis, evaluation, and evaluation checklist